The Prospects of Using Digital Technologies in the Teaching of Labor Protection Science - Rakhimov Octybr Dustkabilovich,; Eshmukhamedov Latif Mahmayusufovich, (European Journal of Life Safety and Stability (2660-9630), 2022)
the article presents the importance and necessity of using digital technologies in the higher education system, the current state of the organization of self-study in the credit-modular system and its organization based on digital technologies and project proposals for the use of educational projects in this area. The content and essence of educational telecommunications projects, its types, methods and stages of effective organization of telecommunications projects, the organization of external evaluation, indicators that differ from foreign analogues of the educational telecommunications project, the creation of which is being designed for the higher education system of Uzbekistan, and the results achieved as the results of practical application are highlighted.